THE IMPACT OF THE BOYCOTT MOVEMENT ON ISRAELI PRODUCTS ON BRAND PERCEPTION AMONG MUSLIM CONSUMERS: AN ANALYSIS OF BRAND IMAGE AND CUSTOMER LOYALTY - Andyan Pradipta Utama; John Christianto Simon; Fitri Nurlaela; Iskandar iskandar; Andi Asy'hary J. Arsyad (Branding: Jurnal Manajemen dan Bisnis, 2023)
This article examines the impact of the boycott movement against Israeli products on brand perception and customer loyalty among Muslim consumers, primarily through an extensive literature review. It investigates how the socio-political context of the boycott influences Muslim consumers' perceptions and attitudes towards these brands. The study synthesizes findings from various scholarly articles, reports, and case studies to understand the dynamics between political activism and consumer behavior. Key insights reveal a notable shift in brand image and loyalty, underscoring the critical role of political and ethical considerations in shaping consumer choices. This comprehensive analysis contributes to the broader discourse on consumer behavior in politically sensitive environments and offers strategic insights for businesses in managing brand reputation amidst socio-political challenges.